A new spodium bond driven coordination polymer constructed from mercury(ii) azide and 1, 2-bis(pyridin-2-ylmethylene)hydrazine. (26th November 2020) - Mahmoudi, Ghodrat; Lawrence, Simon E.; Cisterna, Jonathan; Cárdenas, Alejandro; Brito, Iván; Frontera, Antonio; Safin, Damir A.
Abstract : In this manuscript, the synthesis and X-ray characterization of a new spodium bond driven coordination polymer constructed from mercury(ii ) azide and 1, 2-bis(pyridin-2-ylmethylene)hydrazine are reported. Abstract : In this work we report on a new Hg II coordination polymer [Hg2 L(N3 )4 ] n (1 ), which was readily fabricated from a mixture of Hg(CH3 COO)2, NaN3 and 1, 2-bis(pyridin-2-ylmethylene)hydrazine (L ) in MeOH. Complex exhibits a 1D zig-zag polymeric chain, constructed exclusively through the Hg–N covalent bonds. This chain is formed due to bridging organic ligands L, both coordination pockets of which chelate metal ions, as well bridging end-on coordinated azide anions. The coordination sphere of the Hg II ions is completed by terminal azide anions, yielding a pentacoordinated geometry. The structure of 1 was found to be extended to a 2D supramolecular polymeric layer due to Hg⋯N spodium bonds, formed between neighbouring 1D zig-zag polymeric chains. Due to the spodium bond, the metal cation now exhibits a hexacoordinated geometry. According to the topological analysis, the 2D supramolecular polymeric layer of 1 discloses a uninodal 3-connected hcb (Shubnikov hexagonal plane net/(6, 3)) topology defined by the point symbol of (6 3 ). The 2D supramolecular polymeric layer is further stabilized by intermolecular non-covalent C–H⋯N and N–N⋯π2-Py interactions. Adjacent 2D supramolecular polymeric layers are interlinked through π⋯π stacking interactions between the pyridine rings. The diffuse reflectance spectrum of 1 revealed a broad band, accompanied with a shoulder, in the UV region, corresponding to intraligand transitions, and a broad intense band in the visible region, corresponding to metal-to-ligand charge-transfer. In this work we report on a pivotal role of the Hg II -derived spodium bond on the crystal packing and its characterization using DFT calculations, the quantum theory of atoms-in-molecules and the non-covalent interaction plot computational tools.